Bersama Desa Mangunarga: Membangun Perilaku Hidup Bersih dan Sehat untuk Kehidupan Sejahtera - Mamay Maulana Sobandi; Yakobus Lau De Yung Sinaga; Roganda Situmorang; Isviyanti Isviyanti; Jajang Japar Sodik (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Waste management remains a major challenge in Indonesia, particularly concerning marine plastic waste and the increase in hazardous waste (B3). The lack of understanding and limited facilities such as TPS-3R and waste banks further exacerbate the situation. In response, we conducted a community service program in Mangunarga Village, Sumedang, West Java, aimed at raising awareness and improving waste management practices. This program included educational workshops and equipping waste processing facilities. The results showed a significant increase in community understanding and behavior related to waste management, with awareness rising from 16.5% to 97.2%, and proper waste sorting practices increasing from 8.2% to 96.3%. The success of this program underscores the importance of community-based approaches and supportive infrastructure in addressing environmental challenges at the local level.